2015
DOI: 10.1136/bmjopen-2014-007382
|View full text |Cite
|
Sign up to set email alerts
|

Monetary costs of agitation in older adults with Alzheimer's disease in the UK: prospective cohort study

Abstract: ObjectiveWhile nearly half of all people with Alzheimer's disease (AD) have agitation symptoms every month, little is known about the costs of agitation in AD. We calculated the monetary costs associated with agitation in older adults with AD in the UK from a National Health Service and personal social services perspective.DesignProspective cohort study.SettingLondon and the South East Region of the UK (LASER-AD study).Participants224 people with AD recruited between July 2002 and January 2003 and followed up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“…The symptoms are persistent (374), so that nearly 40% of those with significant agitation still had symptoms six months later (377) and 60% of those with aberrant motor behaviour on the NPI, such as pacing or doing things repetitively, remained symptomatic 18 months later (373). Caring for an agitated person with dementia is more difficult and time consuming that caring for those without agitation; the additional costs of managing agitation account for around 12% of the costs of dementia (412). Figure 11 outlines approaches to managing agitation in dementia.…”
Section: Agitationmentioning
confidence: 99%
“…The symptoms are persistent (374), so that nearly 40% of those with significant agitation still had symptoms six months later (377) and 60% of those with aberrant motor behaviour on the NPI, such as pacing or doing things repetitively, remained symptomatic 18 months later (373). Caring for an agitated person with dementia is more difficult and time consuming that caring for those without agitation; the additional costs of managing agitation account for around 12% of the costs of dementia (412). Figure 11 outlines approaches to managing agitation in dementia.…”
Section: Agitationmentioning
confidence: 99%
“…Agitation, which is commonly observed in people with dementia (PWD) in nursing homes [1,2,3,4,5], may have many negative impacts on the PWD [6,7,8], their caregivers [9,10,11], and society [12]. Acupressure is a therapy that originates from traditional Chinese medicine (TCM).…”
Section: Introductionmentioning
confidence: 99%
“…The present study focuses on the incremental costs of institutionalization, but agitation may be associated with a much higher overall burden. A study in the United Kingdom estimated that the additional costs of managing agitation accounted for approximately 12% of the costs of dementia or £4091 ($7236) per individual with AD when including additional components such as health care costs [33]. In the US setting, a recent claims‐based retrospective study found that patients with dementia and behavioral disturbances including agitation had a higher prevalence of comorbidities, greater use of comedications, and greater health care utilization, resulting in higher health care costs ($9644) compared with patients with dementia without behavioral disturbances.…”
Section: Discussionmentioning
confidence: 99%